Methylphenidate Use and Infectious Diseases in Children With Attention Deficit and Hyperactivity Disorder: A Population-Based Study - Chen, Vincent Chin-Hung; Kao, Kai-Liang; Chen, Yi-Lung; Wu, Shu-I; Lee, Min-Jing; Gossop, Michael (Frontiers in Medicine, 2022)
Objective Children with attention deficit hyperactivity disorder (ADHD) have more visits to the emergency department (ED) due to injuries than those without ADHD. However, no study has investigated whether children with ADHD have more ED visits or hospitalizations due to infectious diseases (IDs) and whether methylphenidate (MPH) treatment may reduce the risk. Method The incidence of ID-related ED visits or hospitalizations was defined as the main outcome. The Cox regression and conditional Poisson regression models were calculated to estimate hazard ratios (HRs) in the population level and relative risks for the self-controlled case series design, respectively. Results Children with ADHD had higher rates of emergency visits (HR = 1.25, 95% CI: 1.23 1.27) and hospitalizations (HR = 1.28, 95% CI: 1.26 1.31) due to IDs than those without ADHD. In the ADHD subgroup, those who received MPH treatment have a reduced risk of emergency visits (HR = 0.10, 95% CI: 0.09 0.10) and hospitalizations (HR = 0.73, 95% CI: 0.71 0.75), compared to those without treatment. The risk of ID-related emergency visits decreased to 0.21 (95% CI: 0.21 0.22); and hospitalizations decreased to 0.71 (95% CI: 0.69 0.73). Within self-controlled analysis, it is demonstrated that compared with non-MPH exposed period, children with ADHD had significantly decreased risks for infection-related emergency visits (RR = 0.73, 95% CI: 0.68 0.78) or hospitalizations (RR = 0.19, 95% CI: 0.17 0.21) during MPH-exposed periods. Conclusions and Relevance This is the first study that reported an increased risk of ID-related healthcare utilizations in children with ADHD compared to those without, and that such risks may be significantly reduced in ADHD children that received MPH treatment.